Laser hardening studies on 50CrMo4 steel at different surface conditions - Ng, Jonye (2018)
Steel is a material used across many industries, such as the construction, automotive and aerospace industries, among many others. [1, 2] Depending on its use, steel can be modified in many ways to change its physical and chemical properties. The are many different processes being used to change the properties of steel, including laser surface treatment. [3] This project investigated how various parameters affect the properties of 50CrMo4 steel. For the project, samples treated under the various parameters were compared with a reference sample, one without any prior surface preparation. Two samples with the same surface preparation but varying magnitude was also compared. The values taken into consideration are the size and hardness of the laser affected area. The parameters include underwater treatment, a layer of graphite coating, pre-oxidation of the material before laser surface treatment, as well as the use of a different purging gas in carbon dioxide (CO2) instead of Argon (Ar). The experimental results reflected that conducting the treat underwater would improve hardness due to the increased rate of cooling. However, if the layer of water is too thick, the energy from the laser will be reflected and refracted away from the sample and there will be no laser hardening effect. A layer of graphite coating will improve the hardness due to carbon diffusion. However, if the sample is too thick, the high carbon content will cause eutectic microstructures to be formed, thus decreasing hardness, albeit with a larger laser affected area. Pre-oxidation of the steel increased the effectiveness of laser surface hardening. A deeper oxide layer increases the surface absorptivity of steel. Using CO2 as a purging gas will produce similar results to Ar gas, with a similar size but higher hardness. Using CO2 as the purging gas means there will be no carbon loss or introduction while using Ar, an inert gas, prevents surface oxidation of the specimen.